2022
DOI: 10.14746/ssllt.2022.12.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Taking stock: A meta-analysis of the effects of foreign language enjoyment

Abstract: Studies examining the positive emotion of foreign language enjoyment (FLE) have recently increased exponentially, as researchers are applying the tenets of positive psychology in applied linguistics. It is therefore an appropriate time to take stock of the current literature and conduct a preliminary meta-analysis. The relationships between FLE and four variables, namely, foreign language anxiety (FLA), willingness to communicate (WTC), academic achievement, and self-perceived achievement were examined. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 46 publications
5
57
0
Order By: Relevance
“…Finally, FL enjoyment was found to be positively associated with ELP, which implied that learners who enjoyed learning English would be able to achieve higher learning gains. This result was in line with the prior research reporting that there existed a positive correlation between FL enjoyment and FL achievements among Chinese middle school students (Wei et al, 2019 ), high school students (Jin and Zhang, 2018 ; Li, 2019 ; Liu and Wang, 2021 ), and university students (Zhang et al, 2020 ; Guo, 2021 ), Korean students (Lee, 2020 ), in other international contexts (Dewaele and MacIntyre, 2014 ; Dewaele and Alfawzan, 2018 ), and in the recent meta-analysis (Botes et al, in press ). Based on the broaden-and-build theory (Fredrickson, 2001 ), when students enjoy learning a foreign language, their horizons of thought are expanded, and they tend to apply various learning strategies, which promotes language learning efficiency (Jin and Zhang, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, FL enjoyment was found to be positively associated with ELP, which implied that learners who enjoyed learning English would be able to achieve higher learning gains. This result was in line with the prior research reporting that there existed a positive correlation between FL enjoyment and FL achievements among Chinese middle school students (Wei et al, 2019 ), high school students (Jin and Zhang, 2018 ; Li, 2019 ; Liu and Wang, 2021 ), and university students (Zhang et al, 2020 ; Guo, 2021 ), Korean students (Lee, 2020 ), in other international contexts (Dewaele and MacIntyre, 2014 ; Dewaele and Alfawzan, 2018 ), and in the recent meta-analysis (Botes et al, in press ). Based on the broaden-and-build theory (Fredrickson, 2001 ), when students enjoy learning a foreign language, their horizons of thought are expanded, and they tend to apply various learning strategies, which promotes language learning efficiency (Jin and Zhang, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Seligman and Csikszentmihalyi ( 2000 ), positive emotion is one of the foundations of positive psychology. Among the several positive emotions, one aspect that has recently come to the forefront in FL learning is FL enjoyment (MacIntyre et al, 2019 ; Dewaele and Li, 2020 ; Botes et al, in press ). Dewaele and MacIntyre ( 2016 ) conceptualized enjoyment as a “complex emotion, capturing interacting dimensions of challenge and perceived ability that reflect the human drive for success in the face of difficult tasks” (p. 217).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The fear was that the sole reliance on online teaching would dampen learners' positive emotions and exacerbate their negative emotions, affecting their learning and coping strategies [5]. Recent research on learner emotions has indeed shown that positive emotions are moderate positive predictors of foreign language (FL) performance, while negative emotions are negative predictors [6,7]. Learners' emotions have been found to be dulled in ERT classes compared to in-person classes.…”
Section: Introductionmentioning
confidence: 99%